MOTIVATION: FROM CONCEPT TO APPLICATIONS: A BIBLIOMETRIC ANALYSIS - Kurnia Arumdani; Sopiah (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
Employee motivation in the company must be the main indicator that is considered in managing human resources. With the attention of superiors to subordinates, it will maintain and be able to manage the motivation of subordinates in doing work, in achieving organizational goals. The application of job characteristics will have a good impact on employees in improving the quality of optimal performance. The use of motivation: from concept to applications has not been investigated using bibliometrics in providing good references by further researchers. The purpose of this study is to provide an extensive bibliometric literature study on motivation. Articles were quoted from the publish or perish database, from 150 articles found from 2017 to 2021, there were 38 articles analyzed in the study. After managing the database, the researchers performed classification and visualization using VOSviewer software to be able to analyze co-authorship, co-occurrence, and citations. Overall, this literature study provides an appropriate reference for further research on the topic of motivation: from concept to applications